Synthesis of tetrazole-containing chlorohydrins and epoxides - Grigoriev, Yuri V.; Yurkova, Yulia M.; Grigorieva, Inna M.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2024)
The alkylation of NH-unsubstituted tetrazoles and 1-substituted 5-mercaptotetrazoles with epichlorohydrine followed by dehydrochlorination of the resulting chlorohydrins was found to be a convenient method for the preparation of tetrazole-containing epoxides. Alkylation reaction was shown to proceed with a yield more than 90 %, both in the presence of bases as a catalyst and without the catalytic action of bases using excess of epichlorohydrine. Alkylation with epichlorohydrine in the absence of bases as a catalyst is more preferable in terms of formation of by-products and, as a consequence, purification of target compounds. Tetrazolylepoxides can also be obtained by a two-step process involving hydroxybromination of tetrazole-containing alkenes to form intermediate bromohydrins and subsequent dehydrobromination of latter.
Keywords: tetrazole derivatives; functionalisation; chlorohydrins; epoxides; synthesis